2000
DOI: 10.1159/000016744
|View full text |Cite
|
Sign up to set email alerts
|

Shape, Orientation and Spacing of the Primary Epidermal Laminae in the Hooves of Neonatal and Adult Horses <i>(Equus caballus)</i>

Abstract: Circumferential and proximodistal variations in the morphology of the primary epidermal laminae of six neonatal and five adult equine feet were documented. Three parameters were quantified: interlaminar spacing, the orientation of the laminae with respect to the overlying wall, and any angulation within the laminae themselves (‘internal angle’). In adult feet, the laminae were most closely spaced at the dorsum, the spacing increasing gradually towards the heels. In foals there was a non-significant trend for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 6 publications
3
40
1
Order By: Relevance
“…2). This morphological variation is consistent with hypotheses of regional loading variability (Douglas and Thomason, 2000;Thomason, et al, 2001) as follows. At the toe, the distal phalanx is thought to pull the laminae down and back, exerting tension on the laminar junction in radial and vertical directions.…”
Section: Biological Responses To Variations In Mechanical Functionsupporting
confidence: 92%
See 3 more Smart Citations
“…2). This morphological variation is consistent with hypotheses of regional loading variability (Douglas and Thomason, 2000;Thomason, et al, 2001) as follows. At the toe, the distal phalanx is thought to pull the laminae down and back, exerting tension on the laminar junction in radial and vertical directions.…”
Section: Biological Responses To Variations In Mechanical Functionsupporting
confidence: 92%
“…By inference, capsule shape should also affect the distribution of stress and strain magnitudes in the laminar junction and in turn affect laminar morphology. Preliminary evidence is available for this three-way interaction between mechanical behavior and the two intrinsic modifiers, in that there are patterns of correlation between measurements of external hoof shape and those of laminar morphology (Douglas and Thomason, 2000;Thomason et al, 2001). In these two studies, capsule shape was quantified by 20 external measurements, based on a list in Kane et al (1998), and including toe angle (TA; measured between the wall and ground surfaces at the toe in lateral view).…”
Section: Feedback Path From External Shape To Internal Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…Contrastingly, our results showed that both in forelimbs ( Fig.2A) and hindlimbs (Fig.2B), the region of the hoof toe had a greater concentration of primary epidermal laminae, corroborating the studies of Bowker (2003), Bidwell & Bolker (2006) Lancaster et al (2007) and Thomason et al (2008). Douglas & Thomason (2000) mentioned that the hoof toe is the region with the highest stress between the hoof wall and the distal phalanx, the gradual reduction in density of primary epidermal laminae towards the hoof bulb, as observed in the present study, probably is an adaptive response to different stresses in the several regions, once under physiological situations the force imposed in the quarters region would be lower than required in the hoof toe, as well as the stress related to the hoof bulbs is lower than to the quarters.…”
Section: Discussionsupporting
confidence: 90%